Yacon (Smallanthus sonchifolius) flour soluble extract improve intestinal bacterial populations, brush border membrane functionality and morphology in vivo (Gallus gallus). (November 2020) - Martino, Hércia Stampini Duarte; Kolba, Nikolai; Tako, Elad
Graphical abstract: Highlights: Yacon flour soluble extract (YFSE) increased the relative abundance of bifidobacterial and Lactobacillus . YFSE upregulated the expression of iron and zinc transporters. YFSE decreased gene expression of inflammation marker and hepcidin. YFSE increased glycogen concentration in pectoral muscle. YFSE improved BBM functionality and intestinal morphology. Abstract: This study evaluates the effects of intra-amniotic administration of yacon (Smallanthus sonchifolius) flour soluble extracts (YFSE) on intestinal bacterial populations, brush border membrane (BBM) functionality and morphology, by using the Gallus gallus model. The YFSE increased (p < 0.05) relative abundance of Lactobacillus, Bifidobacterium, Clostridium and E. coli compared to 18MΩ H2O. The YFSE had systematic effect on BBM functionality, via the upregulation of zinc (zinc transporters – ZnT1, ZnT7 and ZIP9) and iron (ferroportin, Duodenal cytochrome (DcytB) transporters, sucrose isomaltase (SI), and down regulation of Interleukin 1 beta (IL1β), and hepcidin genes expression when compared to the inulin administered group. The YFSE administration increased glycogen concentrations in pectoral muscle compared to noninjected and 18 Ω H2O groups, however, did not change gene expression of enzymes related to glycolysis (phosphofructokinase) and gluconeogenesis (glucose-6 phosphatase). The YFSE increased the depth of crypts, crypt goblet cell diameter, number and type (acidic), and villi goblet cell diameter and type (acidic) when compared to all other groups. Thus, YFSE demonstrated prebiotic effects resulting in improving intestinal bacterial populations profile, BBM functionality, digestive and absorptive capabilities, intestinal morphology, glycogen status and immune system.